2017
DOI: 10.1007/s10695-017-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic high stocking density on liver proteome of rainbow trout (Oncorhynchus mykiss)

Abstract: The main aim of the present study was to assess the effects of chronic high stocking density on liver proteome of rainbow trout. Rainbow trout juveniles (42.6 ± 2.3 g average body weight) were randomly distributed into six tanks at two stocking densities (low stocking density (LD) = 20 kg m and high stocking density (HD) = 80 kg m). Both treatments were performed in triplicate tanks for a period of 60 days. High stocking density caused a reduction in the growth performance compared with LD fish. Lysozyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
5
18
1
Order By: Relevance
“…Cortisol is the most commonly used physiological indicator of the primary response to stress [21]. However, it has been shown that this corticosteroid is not a reliable biomarker of long-term stress exposure [27,[35][36][37]. In this study, Gilthead seabream that endured high stocking densities over 54 days showed a possible reconfiguration of the cortisol response.…”
Section: Discussionmentioning
confidence: 76%
“…Cortisol is the most commonly used physiological indicator of the primary response to stress [21]. However, it has been shown that this corticosteroid is not a reliable biomarker of long-term stress exposure [27,[35][36][37]. In this study, Gilthead seabream that endured high stocking densities over 54 days showed a possible reconfiguration of the cortisol response.…”
Section: Discussionmentioning
confidence: 76%
“…The results of this study also demonstrated that high rearing density without dietary supplementation (Control group) produced a chronic stressful situation. The stress caused by high‐density activates metabolic changes (activation of the catabolic pathways and mobilization of energy stores) to cope with the higher energy requirements (Lupatsch, Santos, Schrama, & Verreth, ; Suárez et al, ; Vijayan et al, ) therefore accelerates the metabolic rate of fish (Barton & Iwama, ) and suppresses fish growth (Naderi et al, ; Suárez et al, ; Vijayan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rearing density is an important topic for the productivity and profitability of rainbow trout farms. We previously found that chronic high rearing density (80 kg/m 3 ) can negatively affect the growth performance, humoral immune responses and liver antioxidant status of rainbow trout (Naderi, Keyvanshokooh, Salati, & Ghaedi, ). High rearing density can produce undesired side‐effects and activate stress response (Wendelaar Bonga, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol has been the most commonly used physiological indicator of the primary response to stress (21). However, there is a shred of evidence indicating that this corticosteroid is not a reliable biomarker of long-term stress exposure (27,(35)(36)(37). In this study, Gilthead seabream exposed to high stocking densities during 54 days showed a possible reconfiguration of the cortisol response.…”
Section: Discussionmentioning
confidence: 68%